-2(4-7x)-2(x-1)=10x

Simple and best practice solution for -2(4-7x)-2(x-1)=10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4-7x)-2(x-1)=10x equation:


Simplifying
-2(4 + -7x) + -2(x + -1) = 10x
(4 * -2 + -7x * -2) + -2(x + -1) = 10x
(-8 + 14x) + -2(x + -1) = 10x

Reorder the terms:
-8 + 14x + -2(-1 + x) = 10x
-8 + 14x + (-1 * -2 + x * -2) = 10x
-8 + 14x + (2 + -2x) = 10x

Reorder the terms:
-8 + 2 + 14x + -2x = 10x

Combine like terms: -8 + 2 = -6
-6 + 14x + -2x = 10x

Combine like terms: 14x + -2x = 12x
-6 + 12x = 10x

Solving
-6 + 12x = 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-6 + 12x + -10x = 10x + -10x

Combine like terms: 12x + -10x = 2x
-6 + 2x = 10x + -10x

Combine like terms: 10x + -10x = 0
-6 + 2x = 0

Add '6' to each side of the equation.
-6 + 6 + 2x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 0 + 6
2x = 0 + 6

Combine like terms: 0 + 6 = 6
2x = 6

Divide each side by '2'.
x = 3

Simplifying
x = 3

See similar equations:

| 4z^2-20z+15=0 | | 4.2=k/2 | | 7x+18y=25 | | 3k+9=k+15 | | q/5-7=10 | | 3/(x-4)=5/x | | -4(z-1)=-3(z+4) | | 0.8h+0.26=7.1-0.72h | | (6x-13)(2x+1)= | | x+y=5.3 | | 7(8-6)2= | | (11/8)-(2/3) | | 3.4m+8=4.9-5.3m | | -193f=-82 | | -193f=82 | | f(x)=x^3-4x^2+25x-100 | | 126=d+0.5d | | -27(4/7)f=9(1/9) | | 10+6w= | | 6x-2=-4-2x | | 5.8-3.6= | | (5+A)+A=100 | | (-7)=6-(9-b) | | 89x=100y | | (-4a)+3+5a=10-18 | | 7x-4y=-18 | | 21-3x=9-(24) | | 12/40=x/3000 | | 5x+24=44 | | (u-1)(u-1)=2u^2+u-17 | | (x-3)(x-3)=2x^2-2x-12 | | 3y-23-6y+37= |

Equations solver categories